2017
DOI: 10.1667/rr14608.1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Circulatory Diseases and other Non-Cancer Outcomes among Nuclear Workers in France, the United Kingdom and the United States (INWORKS)

Abstract: Positive associations between external radiation dose and non-cancer mortality have been found in a number of published studies, primarily of populations exposed to high-dose, high-dose-rate ionizing radiation. The goal of this study was to determine whether external radiation dose was associated with non-cancer mortality in a large pooled cohort of nuclear workers exposed to low-dose radiation accumulated at low dose rates. The cohort comprised 308,297 workers from France, United Kingdom and United States. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 49 publications
8
121
0
6
Order By: Relevance
“…The current study adds to the evidence relating to the risk of CD and low-level exposure to radiation, recently reviewed by Azizova, et al (17,23) and Little (16). The pattern of results from studies of CD after low or moderate acute doses and protracted exposures at low dose rates does not point to an obvious explanation, causal or otherwise, for the reported associations (42)(43)(44)(45)(46)(47). Studies of CD in the Japanese atomic bomb survivors have produced results that do not invite a straightforward interpretation because of, inter alia, substantial variation of risks between disease subtypes (42)(43)(44).…”
Section: Comparison With Previous Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…The current study adds to the evidence relating to the risk of CD and low-level exposure to radiation, recently reviewed by Azizova, et al (17,23) and Little (16). The pattern of results from studies of CD after low or moderate acute doses and protracted exposures at low dose rates does not point to an obvious explanation, causal or otherwise, for the reported associations (42)(43)(44)(45)(46)(47). Studies of CD in the Japanese atomic bomb survivors have produced results that do not invite a straightforward interpretation because of, inter alia, substantial variation of risks between disease subtypes (42)(43)(44).…”
Section: Comparison With Previous Studiessupporting
confidence: 52%
“…Studies of Russian ''liquidators'' of the Chernobyl accident have reported raised risks of CD incidence with respect to external dose, but based on a surprisingly high proportion of cases among the liquidators (45,46). The authors of the recent INWORKS analysis of CD mortality among nuclear workers (including those from Sellafield), which showed significantly increased ERR/Sv external dose, warned that heterogeneity of risks did not permit firm conclusions to be drawn (47). The findings of the current study reinforce the need for a careful interpretation of a complex set of results, and for future studies to address outstanding issues, such as the influence of major non-radiation risk factors for CD on reported radiation-associated risk estimates.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Thus, neutron exposure data are likely to be incomplete and some exposure misclassification is unavoidable in this study. Although neutron exposures are likely to be small in relationship to those from photons (42), additional research is needed to understand the effects of neutrons in this study and in other studies of populations exposed to mixed radiation fields.…”
Section: Discussionmentioning
confidence: 99%
“…Au sein d'une cohorte, des analyses de relation dose-risque peuvent être menées pour l'ensemble des causes de décès (Leuraud et al, 2015 ;Richardson et al, 2015 ;Gillies et al, 2017b). Si l'on souhaite approfondir l'étude d'une pathologie en particulier, par exemple le cancer du poumon (Leuraud et al, 2011 ;Grellier et al, 2017) ou les pathologies de l'appareil circulatoire (Drubay et al, 2015), et recueillir des données complémentaires sur les facteurs de risque de cette pathologie comme par exemple, le tabagisme (Leuraud et al, 2011), la glycémie, l'indice de masse corporelle ou l'hypertension (Drubay et al, 2015), la conduite d'une étude cas-témoins nichée dans une cohorte peut constituer une alternative efficiente.…”
Section: Méthodesunclassified
“…Cette cohorte a récemment été incluse dans l'étude internationale INWORKS rassemblant plus de 300 000 travailleurs du nucléaire de trois pays (France, Royaume-Uni et États-Unis) (Hamra et al, 2016). L'étude INWORKS a mis en évidence une augmentation du risque de décès associé à la dose cumulée de rayonnements ionisants pour les leucémies (Leuraud et al, 2015), les cancers solides (Richardson et al, 2015) et les maladies de l'appareil circulatoire (Gillies et al, 2017b). Pour les cancers, les coefficients de risque estimés dans INWORKS sont cohérents avec les coefficients de risque dérivés du suivi de la cohorte des survivants des bombardements d'Hiroshima et de Nagasaki, sur lesquels reposent les hypothèses sous-jacentes au système de radioprotection actuellement en vigueur (ICRP, 2007).…”
Section: Cohortes Cea-areva Nc Et Edfunclassified